2012
DOI: 10.1001/archpediatrics.2011.198
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Single Home Nursing Visits vs Office-Based Care After Nursery/Maternity Discharge

Abstract: To compare office-based care (OBC) with a care model using a home nursing visit (HNV) as the initial postdischarge encounter for "well" breastfeeding newborns and mothers.Design: Randomized controlled trial.Setting: A single academic hospital.Participants: A total of 1154 postpartum mothers intending to breastfeed and their 1169 newborns of at least 34 weeks' gestation.Interventions: Home nursing visits were scheduled no later than 2 days after discharge; OBC timing was physician determined.Outcome Measures: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 63 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…24 , 25 HV programs may be funded by community resources, federal or local grants or insurance companies, based on family income criteria and consent to participate. 20 , 47 , 48 , 49 , 50 , 51 , 52 Community-based HV programs may provide financially eligible families with parenting education and support services before delivery.…”
Section: Hv Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…24 , 25 HV programs may be funded by community resources, federal or local grants or insurance companies, based on family income criteria and consent to participate. 20 , 47 , 48 , 49 , 50 , 51 , 52 Community-based HV programs may provide financially eligible families with parenting education and support services before delivery.…”
Section: Hv Servicesmentioning
confidence: 99%
“…49 , 50 Visiting nurses were also identified as a viable means of securing high-quality patient-centered outcomes and found to be as effective and safe for initial patient encounters post-hospital discharge as traditional office visits. 52 …”
Section: Hv Servicesmentioning
confidence: 99%
“…In jurisdictions such as New Zealand, Australia, Canada and the UK, home-visits done by nurses, midwives and peers are available for mother-baby dyads and have been studied thoroughly in the past decade [ 5 8 ]. Home-visits, while recognized for achieving high maternal satisfaction, also produce equivalent clinical outcomes for mothers and newborns as hospital-based follow-up [ 9 10 ]. Postpartum home-visits may also decrease newborn hospital admissions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present integrative review, two (22.2%) of the articles (11)(12) were found in the year 2012. It is emphasized that no production was found that responded to the guiding question of the study, between 2000 and 2007.…”
Section: Resultsmentioning
confidence: 74%
“…To identify and analyze, from the perspective of nurses, the process of axiological evaluation of the promotion, protection and support to breastfeeding. (55.5%) (12)(13)(14)(15) ; one (11.1%) in Portugal (16) ; one (11.1%) developed in Australia (17) ; one (11.1%) in Pennsylvania (18) ; one (11.1%) in the United States of America (11) . Figure 2 summarizes the articles of the final sample, which were presented in chronological order to better explain the evolution of the subject under investigation.…”
Section: Le= VI Dr= Weakmentioning
confidence: 99%